POTENSI Trichoderma harzianum DALAM MENGENDALIKAN SEMBILAN ISOLAT Fusarium oxysporum SCHLECHT. f.sp. zingiberi TRUJILLO PADA KENCUR - Albertus Kurniawan Edi Prabowo; Nur Prihatiningsih; Loekas Soesanto (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2006)
The research aimed to compare the effect of adding biological control agent Trichoderma harzianum on nine chosen isolates of Fusarium oxysporum f.sp. zingiberi in planta and yield of Kaempferia galanga was carried out at the screen house from January up to July 2005. Randomized Block Design was used with three repliactes. Result of the research indicated that T. harzianum could be able to prolong incubation period, to decrease disease intensity, to decrease virulency level, to decline number of late conidia, and to increase rhizome weight in the range of 4-30,6 dai (days after inoculation), 7.89-56.25%, low to high, 0.32-1.95 ´ 107 conidia g-1 soil, and 0.23-4.95 g per polybag, respectively. AddingT. harzianum could potentially be developed as biological control agent of Fusarium ozysporum f.sp. zingiberi.